Induced pluripotent stem cells and genome editing technology as therapeutic strategies for Duchenne muscular dystrophy - Irwan Saputra Batubara (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Duchenne muscular dystrophy (DMD) is a rare genetic, progressiveand devastating skeletal and cardiac muscle disorder due to mutationof the dystrophin gene that affects 1 in 3500 young males. Currently,there is no curative management for this pathology. The development ofinducedpluripotent stem cells (iPSCs) offers a promising cell-based strategyfor the treatment of muscular dystrophy. Several techniques have beenestablished to generate functional myogenic progenitor cells derived fromiPSCs. In addition, technologies in genetic modification using ZFN, TALENs, orCRISPR/Cas9 demonstrate potent methods to restore dystrophin expression.However, current evidence shows that either iPSCs or gene editing carrya risk of oncogenesis caused by the integration of exogenous DNA into therecipient gene. Thus, the safety issue is a major challenge for translatingthis method into human clinical applications. This review briefly discussedrecent developments and progressions of iPSCs as well as genome engineeringtechnologies relevant to regenerative medicine, especially for the treatmentof DMD.